"Lá vem chegando São Sebastião, vem aqui te visitar": festas, andanças e folias no interior goiano (1960/2013) - Oliveira, Anderson Aparecido Gonçalves de (2014)
The present dissertation seeks understanding the experiences of people from the goiano interior, specially in the rurais areas affected by UHE Serra do Facão from the religious festive practices having as a honored saint São Sebastião. The focus of the analysis will be the practical and rural knowledge Running along through religiosity of these actors as an expression of their ways of life so taht we can analyze how these factors as an expression of their ways of life so that we can analyze how these factors makes emerge cooperative relationships, identity links in its various forms of sociability, those tat are quite significant and widespread cultural brands during the celebrations, whether devotional or not, especially in rural communities where such relationships are narrowed, ths providing for that communities: Mata Preta, Anta Gorda, Lagoinha e Fazenda Pires, all rural areas of district of Catalão-GO, goinano southwest.